(untitled) (Acta Education, 2023)
This article examines the phenomenon of education in the context of Karl Popper’s theory of open society. Open society, based on the principles of democracy, freedom, and critical thinking, strives for continuous progress and self-improvement. Education plays a central role in this process by developing individuals’ skills in critical thinking, information analysis, and questioning. It also promotes accessibility and inclusivity, ensuring equal opportunities for all individuals to receive quality education, regardless of their social status or characteristics. An important aspect is the scientific approach in education, which stimulates the exploration and testing of hypotheses, as well as openness to new ideas. The phenomenon of education within the framework of the theory of open society aims to cultivate active citizens capable of self-development, making informed decisions, and participating in the democratic process. This article highlights key aspects of the phenomenon of education in an open society and emphasizes its significance for the development of a progressive and inclusive society.